Inhibiting carbonate formation using CO2–CO–C2+ tandems. (2nd July 2021) - Wang, Ning; Yao, Kaili; Vomiero, Alberto; Wang, Yuhang; Liang, Hongyan
Abstract : Electrochemical reduction of CO2 (CO2 RR) has great potential to transform the petrochemical sector toward sustainability and to mitigate greenhouse gas emissions. However, direct CO2 RR suffers from carbonate formation, which brings a dramatic rise in the energy consumption. By quantitative energy analysis, the idea of using CO2 ‐CO‐C2+ tandems can avoid the energy penalty caused by carbonate formation and improve total energy efficiency. Thus, proposed carbonate‐free system is of great importance for commercial CO2 RR economic viability